2021
DOI: 10.3390/ijerph18168380
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Association of Self-Perceived Physical and Social Neighborhood Environment with Health of Chinese Rural Residents

Abstract: (1) Objectives: Using cross-sectional datasets, we investigated whether better self-perceived physical and social neighborhood environment was associated with perceived health status and health-related behaviors among Chinese rural residents. (2) Study Design: The study was based on the 2016 China Family Panel Studies (CFPS) survey. The sample consisted of 7191 rural residents over 18 in China. (3) Methods: The article measured physical neighborhood environment from the two aspects of dwelling environment (DE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Furthermore, residents who perceived living in areas with clean air were more likely to report good health. Our findings are consistent with earlier studies 32 33 55. Poor air quality could cause respiratory infections 35 56.…”
Section: Discussionsupporting
confidence: 94%
“…Furthermore, residents who perceived living in areas with clean air were more likely to report good health. Our findings are consistent with earlier studies 32 33 55. Poor air quality could cause respiratory infections 35 56.…”
Section: Discussionsupporting
confidence: 94%
“…The human social setting is impossible without the neighbourhood environment. A residential area's convenience, safety, and advancement can affect residents' health [24]. The most significant associations in our study were found between the perceived neighbourhood environmental factors and BMI, PA, stroke, stress, and harmful habits.…”
Section: Discussionmentioning
confidence: 49%
“…It is a relatively comprehensive and representative indicator, although the self-rated health status may be easily affected by the individual's socioeconomic characteristics and subjective [ 27 ]. It is more accurate than objective indicators to some extent [ 28 , 29 ]. In the CLDS questionnaire, the interviewees were asked “What do you think of your current health?” We define the variable healthy based on the question “What do you think of your current health?” in the CLDS questionnaire: healthy = 1, if the interviewee answers “very healthy” or “healthy,” and 0 otherwise.…”
Section: Methodsmentioning
confidence: 99%